THE IMPACT OF ARTIFICIAL INTELLIGENCE (AI) IN PRODUCT VISUAL CONTENT ON CONSUMERS' MENTAL IMAGERY, PRODUCT EVALUATION, POSITIVE EMOTIONS, AND PURCHASE INTENTION - Arief Nugraha, Taufiq
Artificial Intelligence (AI) can be utilized to assist the marketing of Small and Medium Enterprises (SMEs) that have limitations in creating visual product content that appeals to consumers. This study aims to investigate the differences between consumer evaluations of products with AI-generated backgrounds and fully human results. This study examines consumer response evaluation from the perspective of mental imagery, product evaluation, positive emotion, and purchase intention variables using the S-O-R (stimulus-organism-response) framework. The stimulus tested was the visual content of product photos with AI-generated and human backgrounds. Data were obtained from 197 participants aged 18-45 years (M = 25) through an online experimental questionnaire using a 2 (background generator: AI vs. human) × 2 (setting: outdoor vs. indoor) between subject design with the disclosure that the stimulus was AI-generated. Wilcoxon, Mann-Whitney, PLS-SEM, and PLS-MGA statistical methods were used to test the hypotheses. The findings showed that consumers' evaluations of AI-generated products were not significantly different (p > 0,05) compared to human results in the responses of mental imagery, product evaluation, positive emotion, and purchase intention. Mental imagery can increase purchase intention through good product evaluation and elicit positive emotion responses to AI-assisted product visual content. In addition, there was no difference in the strength of the variable relationships between the two groups. The conclusion of this study is that product visual content with AI background has the same good consumer response as human results. The practical implication of this study is the suggestion for SMEs to use AI to help create product visual content that is faster, more attractive, and can increase consumer purchase intention.